PROFILE OF STUDENT ACADEMIC BUOYANCY VIEWED FROM THE LAMPUNG SUB-CULTURE, INDONESIA - Mawarni, Anisa; Febriyani, Tika; Rogamelia, Risna (Universitas Pendidikan Indonesia, 2024)
Research related to academic buoyancy so far has been more centered on Western culture, especially in the secondary school realm. Indonesia is a plural country that requires studies and information to encourage academic success and focuses on the positive development in Guidance and Counseling services. This study describes the level of buoyancy in the student context in terms of the Lampung subculture, namely the various tribes in Lampung Province such as the Javanese, Lampung Papedun and Lampung Saibatin, Malay, Minang, and Ogan. The method of the research uses quantitative survey research types. The correspondence of the research is 500 students from 4 (four) major universities in Lampung Province. The Academic Buoyancy Instrument used in this research is adapted from the theory of Marsh Martin, and Smith (2019). Data analysis used Rasch model analysis with Winsteps program and descriptive analysis. The results had academic buoyancy in the moderate category for each indicator with different indicator values for each ethnic group in Lampung Province. This research shows that there are indicators of academic buoyancy that do not fully occur in tertiary institutions